2021
DOI: 10.3390/ijerph18010285
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure and Tooth Loss: A Large Cross-Sectional Study with Age Mediation Analysis

Abstract: We aimed to investigate the association between blood pressure (BP) and tooth loss and the mediation effect of age. A cross-sectional study from a reference dental hospital was conducted from September 2017 to July 2020. Single measures of BP were taken via an automated sphygmomanometer device. Tooth loss was assessed through oral examination and confirmed radiographically. Severe tooth loss was defined as 10 or more teeth lost. Additional study covariates were collected via sociodemographic and medical questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 67 publications
3
30
1
Order By: Relevance
“…When it comes to the association of missing teeth with systemic health parameters in PD patients, a positive association was found with BP levels, as previously reported [ 34 , 56 , 57 ]. However, there was no significant data supporting an association between Hba1c and the number of missing teeth, contradicting literature on the edentulism–DM link abovementioned [ 55 ].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…When it comes to the association of missing teeth with systemic health parameters in PD patients, a positive association was found with BP levels, as previously reported [ 34 , 56 , 57 ]. However, there was no significant data supporting an association between Hba1c and the number of missing teeth, contradicting literature on the edentulism–DM link abovementioned [ 55 ].…”
Section: Discussionsupporting
confidence: 83%
“…Firstly, the study sample was acquired from a large representative U.S. population survey, from a vast collection of datasets through an 18-year time span (2001–2018). Additionally, our research aimed to evaluate a previously proven association between BP and tooth count [ 34 ], but this time in a group of patients taking PD-based medication. Notwithstanding and despite the reproducibility of the study design, the final included sample was relatively small.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the number of teeth, 10 studies evaluated the number of missing teeth [32][33][34][35][36][37][38][39][40]51 and 10 studies evaluated the number of remaining teeth [41][42][43][44][45][46][47][48][49][50] . In the analyses, only four studies used measured values [34][35][36]40 while the other 16 categorized measured values.…”
Section: Literature Searches and Study Characteristicsmentioning
confidence: 99%
“…For all the studies, there was a clear focus. Five of the studies (cross sectional) recruited subjects from a clinical setting 32,35,38,42,43 , which has a higher risk of selection bias. Seven studies used self-reported information on the number of teeth and four studies used self-reported information for hypertension in their analyses, which lowed the rating.…”
Section: Quality Evaluation For Each Articlementioning
confidence: 99%